Perkembangan Tari Piriang Di Kanagarian Pandai Sikek Kecamatan X Kotokabupaten Tanah Datar - Nofri Hidayat; Afifah Asriati (SENDRATASIK UNP, 2020)
This study belongs to a qualitative research using a descriptive analysis method. The object of this research was the Piriang dance in PandaiSikek village, X Koto district, TanahDatar regency. The research instrument was the researcher itself and was assisted by stationeries, a photo camera, a handy cam, and aflash drive. The data were collected through literature study, observation, interview, and documentation. The data analysis was done by collecting the data, grouping the data, analyzing the data, interpreting the data, and reporting the results of the research.  The results of this study show that the Piriang dance in PandaiSikek village, X Koto district, Tanah Datarregency, has two aspects of development: quantitative and qualitative aspects. Quantitative development is found in the number of actors who have increased from generation to generation. Judging from the area of its use, apart from PandaiSikek, it is also performed inKacang village. Meanwhile, its functions and uses have developed.  In thebeginning, it was only danced in the harvest time. Today,it is performed in various events such as wedding ceremonies, circumcisions, Khatam Qur’an (sealing the Koran), and other events. Meanwhile, qualitatively there is a development in movement and costume.